Crystal Structure of NLRP3 NACHT Domain With an Inhibitor Defines Mechanism of Inflammasome Inhibition. Issue 24 (3rd December 2021) - Dekker, Carien; Mattes, Henri; Wright, Michael; Boettcher, Andreas; Hinniger, Alexandra; Hughes, Nicola; Kapps-Fouthier, Sandra; Eder, Jörg; Erbel, Paulus; Stiefl, Nikolaus; Mackay, Angela; Farady, Christopher J.
Graphical abstract: Highlights: Molecular details of NLRP3 inflammasome activation/inhibition are not well understood. The crystal structure of the NACHT domain reveals the auto-inhibited state of NLRP3. An MCC950-like NLRP3 inhibitor locks the NACHT domain in an inactive conformation. The work provides structural detail on how NLRP3 can be inhibited by small molecules. Abstract: The NLRP3 inflammasome assembles in response to a variety of pathogenic and sterile danger signals, resulting in the production of interleukin-1β and interleukin-18. NLRP3 is a key component of the innate immune system and has been implicated as a driver of a number of acute and chronic diseases. We report the 2.8 Å crystal structure of the NLRP3 NACHT domain in complex with an inhibitor. The structure defines a binding pocket formed by the four subdomains of the NACHT domain, and shows the inhibitor acts as an intramolecular glue, which locks the protein in an inactive conformation. It provides further molecular insight into our understanding of NLRP3 activation, helps to detail the residues involved in subdomain coordination within the NLRP3 NACHT domain, and gives molecular insights into how gain-of-function mutations de-stabilize the inactive conformation of NLRP3. Finally, it suggests stabilizing the auto-inhibited form of the NACHT domain is an effective way to inhibit NLRP3, and will aid the structure-based development of NLRP3 inhibitors for a range of inflammatory diseases.